2014
DOI: 10.1186/1471-2393-14-291
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spinal anaesthesia for elective caesarean section on uterine and umbilical arterial pulsatility indexes in normotensive and chronic hypertensive pregnant women: a prospective, longitudinal study

Abstract: BackgroundDespite the known effects of neuraxial blockade on major vessel function and the rapid decrease in uterine vascular impedance, it is unclear how the blockade affects the utero-placental circulation in the near-term. We hypothesize that among women with chronic hypertension, a loss of sympathetic tonus consequent to spinal block may cause significant changes in the utero-placental haemodynamics than the changes typical in normal pregnant women. Therefore, the main study objective was to analyse the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
1
5
1
Order By: Relevance
“…They found a decrease in MAP after spinal anaesthesia in both study groups, while the fetal circulatory parameters were unchanged. Their results are in contrast to our findings of a small increase in blood pressure, but may be explained by the fact that Guedes-Martins et al 16 did not infuse a vasoconstrictor to avoid spinal anaesthesia-induced hypotension. Their study supports that vasoconstrictor prophylaxis is necessary to avoid maternal hypotension.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…They found a decrease in MAP after spinal anaesthesia in both study groups, while the fetal circulatory parameters were unchanged. Their results are in contrast to our findings of a small increase in blood pressure, but may be explained by the fact that Guedes-Martins et al 16 did not infuse a vasoconstrictor to avoid spinal anaesthesia-induced hypotension. Their study supports that vasoconstrictor prophylaxis is necessary to avoid maternal hypotension.…”
Section: Discussioncontrasting
confidence: 99%
“…It is not clear whether the participating women were positioned in a left lateral tilt position, the authors did not use invasive monitoring, and it is difficult to compare the results to our study. In line with the findings of Lato et al , 15 Guedes-Martins et al 16 found that spinal anaesthesia induced hypotension at caesarean section, but that hypotension was not associated with altered pulsatility indices in the uterine or umbilical arteries.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In women with a low risk of developing preeclampsia, increased uterine artery PI with notching was the best predictor of overall risk (sensitivity 23 %, specificity 99 %, positive likelihood ratio Other factors apart from trophoblast invasion also influence uterine blood flow. Additional factors include physical activity [16], local anesthesia [17] but also the location of the placenta [18].…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension occurs within approximately 70-80% of cases as a consequence of sympathetic blockade in the affected areas of anesthesia, which might cause organ and placental hypoperfusion. Acute hypotension reduces cerebral perfusion, which leads to transient ischemia and activates the vomiting center [3][4][5][6]. Fall in CO reduces oxygen delivery to organs and tissues, results in buildup of oxygen debt, causing complications after SA [7,8,9].…”
Section: Introductionmentioning
confidence: 99%